Collaboration and motivation in an online learning environment: students’ perceptions of collaborative activities and attitudes towards online learning - Jorge, Idalina (2013)
The report about distance learning in higher education in Portugal (2009) states that only a small percentage of HE enrolments are in DL courses, that the demand for the modality is growing, and that the Portuguese research in DL needs development, to support innovation in the modality. This study aimed to identify the collaborative activities that the 122 students enrolled in Masters’ courses between 2009-2012, in two Portuguese Universities, considered more motivating, their preferred type of assignment, the tools’ perceived ease of use, the social and cognitive aspects of teamwork, the tutor’s influence on teamwork and preferred team organization. The results indicate that the students feel comfortable participating, interacting and debating and that some collaborative activities such as designing projects, simulations, problem-based activities, discussions and written reports are more motivating than others. The results also show that the students have positive attitudes towards online learning, that online trust takes time to develop, that both face-to-face meetings and videoconference increase trust, though time flexibility is a practical advantage of online collaboration and that the way that collaborative assignments are designed can facilitate or hinder adequate collaboration.